The Influence of Macrovascular and Microvascular Complications on the Quality of Life of Diabetes Mellitus Patients at Mardi Rahayu Kudus Hospital - Caesary, Clara D. (Universitas Padjadjaran, Indonesia, 2025)
Diabetes Mellitus, also known as diabetes, is a chronic disease characterized by blood sugar levels that exceed normal limits. Poor management of diabetes mellitus patients can cause various macrovascular and microvascular complications. Complications in diabetes mellitus sufferers are one of the factors that can affect quality of life. This study aims to determine the effect of macrovascular and microvascular complications on the quality of life of diabetes mellitus patients at Mardi Rahayu Kudus Hospital. The method used in this research is prospective, quantitative research using a cross-sectional approach. Data for quality of life researchers used the WHOQOL-BREF questionnaire. The respondents involved and meeting the inclusion criteria were 104 patients. The results of the study showed that there were macrovascular and microvascular complications. The highest incidence of complications was macrovascular (37.5%), followed by microvascular complications (26.0%), and macrovascular + microvascular complications (36.5%). Meanwhile, the highest quality of life category with complications was the high category at (52.9%) and the moderate category at (47.1%). DM and complications are mostly suffered by women (58.7%), with an average age of 45-65 years. The highest use of antidiabetic therapy includes metformin (53.1%), metformin + glimepiride (31.8%) and glimepiride + metformin + sansulin log-g (21.4%), as well as medication for comorbidities given according to the complications suffered by the patient. patient. Research shows that macrovascular and microvascular complications have no influence on quality of life due to the results of the binary logistic regression test (Sig. > 0.05).